Problem-based learning: experiences in Professional and Technological Education - Castaman, Ana Sara; Tommasini, Angélica (Revista Labor, 2020)
This study aims to learn about the concepts of active methodologies in Professional and Technological Education, in order to report the experience of using Problem-Based Learning (PBL) in the context of the National Program for the Integration of Professional Education with Basic Education, in Youth and Adult Modality (PROEJA), in a federal educational institution. Thus, it is guided by a qualitative research, using the bibliographic technique and the experience report. It is divided into 02 (two) sections: a) it discusses active methodologies as a teaching strategy that can enable integral training at EPT; b) reports the experience of PBL in the context of PROEJA. It is concluded that PBL has a dynamic and strategic bias, which can promote collaborative work, creativity, autonomy, flexibility, commitment and oral communication by students, which is in line with institutional objectives.